Pyjamas are forgiving - Khanna, Twinkle (b, 2018)
Shanthamaaya Sthalam in Kerala is nothing less than the Iron Man of Ayurvedic spas. Here patients have to receive daily shots of ghee laced with cow's urine and he purged both by leeches and the world's most powerful laxative. Anshu, a regular, is a firm believer in the powers of Ayurveda, but on this visit she finds it harder to rebalance herself. For among the milieu of new patients is a familiar and unsettling
Keywords: Divorced men -- Fiction; Husband and wife -- Fiction; Medicine, Ayurvedic -- Fiction